Pt–WO3 porous composite ceramics outstanding for sensing low concentrations of hydrogen in air at room temperature. (2nd March 2017) - Song, Cunbiao; Wu, Guitai; Sun, Beilei; Xiong, Yao; Zhu, Sheng; Hu, Yongming; Gu, Haoshuang; Wang, Yu; Chen, Wanping
Abstract: Pt–WO3 porous composite ceramics have been prepared from Pt and WO3 nanoparticles through pressing and sintering. These ceramics exhibit extraordinary room-temperature sensing capabilities, including high sensitivities, fast response and recovery speeds, and good stability, for low concentrations of hydrogen (at and below 1000 ppm) in air; while for high concentrations of hydrogen (above 2000 ppm) in air, the recoveries in air are only partial in given amounts of time. We propose that for low concentrations of hydrogen, the response results from the reaction of hydrogen with chemisorbed oxygen on WO3 ; while for high concentrations of hydrogen, hydrogen chemisorption on WO3 will occur after all chemisorbed oxygen on WO3 is reacted. The relatively high stability of chemisorbed hydrogen on WO3 is responsible for the observed partial recoveries. Our results show that Pt–WO3 composite ceramics are highly competitive for sensing low concentrations of hydrogen in air at room temperature among various metal oxide semiconductor bulk materials. Highlights: Pt–WO3 composite ceramics are highly competitive for sensing low concentrations of hydrogen in air at room temperature. Pt–WO3 composite ceramics are found to show different recovery behaviors for low and high concentrations of hydrogen. A combined hydrogen sensing mechanism rooted in oxygen and hydrogen chemisorption on WO3 is established.